2006
DOI: 10.18705/1607-419x-2006-12-3-262-267
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives of improvement of compliance - results of open study of adherence of patients to treatment with fixed in one blister combinations of enalapril and indapamide

Abstract: The aim of the study was to evaluate the adherence of patients to treatment with new fixed in one blister combinations of enalapril and indapamide. 115 patients participated in the study. In conclusion, analysis revealed high efficacy of studied combinations, which can be partly explained by high compliance of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The findings of studies of the association between adherence and grade of HT, experience of hypertensive crisis, and duration of HT were not consistent [27, 29, 33, 38–41].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of studies of the association between adherence and grade of HT, experience of hypertensive crisis, and duration of HT were not consistent [27, 29, 33, 38–41].…”
Section: Resultsmentioning
confidence: 99%
“…Adherence was assessed using data from cross-sectional surveys and from baseline data in prospective observational intervention studies. In studies using the MMAS-4 [11–19, 21, 2327, 30, 33] adherence to AHT varied from 1.62 ± 0.27 [11] to 3.12 ± 0.86 points [35] out of a maximum of four (Additional file 3). Among these studies, the highest rates of adherence were found in post-marketing studies, all with large sample sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations